Hannah Arendt - entre o passado e o futuro da política e do direito: autoridade, legitimidade, violência e poder - Hsiao, Marcelo (2007)
Politics permeates all aspects of human dealings in society. This defense advances a jusphilosophical investigation on the reflections of Hannah Arendt in relation to: - Law: the intuition of the just/unjust, licit/illicit, lawful/unlawful and legal/illegal; - Power: its distinction of violence; its correlation with vigor, strength and authority; - Legitimacy: the differences between legitimation and legitimacy, its fundamental of validity, its importance for politics and law. The concepts of power, violence, as well as their correlates: vigor, strength and authority have led to many mistakes. A limiting vision of these concepts would be to view them only from a domain standpoint. What Arendt proposes is to analyze them individually, showing their particularities and the breadth of these concepts in the context of politics. Thus, power, along the lines of Arendt s rationale, corresponds to the human activity to act in unison . It is grounded on the freedom of action and speech, without which the public sphere loses its raison d être. Acting in unison is never the property of an individual, but belongs to a group that keeps it united. When we say that someone is in power , this means that he was sworn-in by a certain number of people to act on his behalf. It is here that power finds its legitimacy. Vigor denotes something in the singular: it is the property inherent to an object or person and belongs to its character. Vigor has a peculiar independence and, for this reason, it is the nature of a group and of its power to turn against independence, the property of individual vigor. Strength, oft confused with violence, should only indicate the energy released by physical or social movements. It is the natural quality of an isolated individual. It is measurable, reliable and unchangeable. In a struggle between two men, the decisive factor is strength, not power